Richard Clayderman Essential - Clayderman, Richard, 1953-; Music Video Distributors, Inc. ([Canadá] : Music Video Distributors, 2005)
Considered by many to be the most popular pianist of all time, this handsome, Paris-born musician has charmed the masses with his brand of light, accessible classical compositions and a highly romantic demeanor. Since 1982 his concerts and records have consistently been voraciously consumed, and the Nancy Reagan-dubbed "Prince of Romance" continues to delight audiences with a dependable output of show tunes, popular classical works, and romantic standards. This collection features some of the artist's most-loved tunes, including two versions of the song that caught Europe's attention for the very first time, "Ballade Pour Adeline."
A Night In Budapest/Hungarian Dance No. 6/Bohemian Melody/Hungarian Dance No. 5/Ballade Pour Adeline -- Piano concerto No. 1B-flat Minor Opus 23 -- Eleana -- There is always, Shunshine above the clouds -- Moonlight sonata -- Christmas concerto -- Desperato -- Chinese garden -- Poetic sonatina -- Smiling Joey -- L for love -- Rhapsody in blue -- Give a little time to your love -- The tenderness -- Lady Di -- The last days of Anastasia Kemsky -- Whispers -- Vanessa's first smiles.
Bonus tracks: Ballade pour Adeline (1981); Childhood memories; Letter to my mother; Ballade pour Adeline (1985).
DISPONIBLE
Interpretan Richard Clayderman y otros músicos.
DVD; NTSC/Region 0.
En inglés.
Keywords: Interpretación del piano; Música instrumental; Música para piano; Música para televisión; Videos musicales